Border blurs - Thomas, Greg (Liverpool University Press, 2020)
This volume considers the relationship between English and Scottish poets and the international concrete poetry movement of the 1950s-1970s, focusing on the work of Ian Hamilton Finlay, Edwin Morgan, Dom Sylvester Houédard and Bob Cobbing. It will be a vital resource for students and scholars of modernism, intermedia art and British literature.
10.3828/liverpool/9781789620269.001.0001
Keywords: Concrete poetry; English; Concrete poetry; English poetry